2012
DOI: 10.3354/meps09643
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incubation temperature on growth performance in Atlantic salmon

Abstract: Interspecific variations in thermal growth performance of ectotherms have received considerable recent interest fueled by the focus on ecological climate change effects. Amongpopulation variations in growth are commonly observed in field studies. However, the role of pheno typic plasticity in shaping this variation is largely unexplored in teleost fishes. Here, we tested for the effect of incubation temperature on thermal scaling of growth and maximum growth performance of the anadromous salmonid Atlantic salm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 57 publications
3
47
1
Order By: Relevance
“…Their short migration distance enables them to have energy to conceive bigger eggs (Crossin et al 2004), which can then compensate for higher incubation temperature. Indeed, others have previously shown that a large yolk mass can buffer against untoward effects of elevated incubation temperature on survival and growth of hatchlings (Beacham and Murray 1985;Ojanguren and Braña 2003;Finstad and Jonsson 2012). We suggest a similar buffering effect on CTmax, a proposition that needs to be experimentally tested but one certainly supported by the significant correlation between egg mass and CTmax demonstrated here, which was independent of incubation temperature.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Their short migration distance enables them to have energy to conceive bigger eggs (Crossin et al 2004), which can then compensate for higher incubation temperature. Indeed, others have previously shown that a large yolk mass can buffer against untoward effects of elevated incubation temperature on survival and growth of hatchlings (Beacham and Murray 1985;Ojanguren and Braña 2003;Finstad and Jonsson 2012). We suggest a similar buffering effect on CTmax, a proposition that needs to be experimentally tested but one certainly supported by the significant correlation between egg mass and CTmax demonstrated here, which was independent of incubation temperature.…”
Section: Discussionsupporting
confidence: 52%
“…Besides the intraspecific differences of hatchling size, increasing incubation temperature reduces fry mass (here and previously, e.g., Beacham and Murray 1985;Ojanguren and Braña 2003;Finstad and Jonsson 2012), likely because of a reduced aerobic scope and capacity for growth (Pörtner 2010). Reduced fry size, however, correlated negatively with CTmax, explaining some of the population variation in CTmax.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…(Quinn et al 2004(Quinn et al , 2011. Our results indicate that it may not be early growth per se, but elevated incubation temperature that increased juvenile growth (Finstad & Jonsson 2012), which is associated with a larger egg size. In the present study, we found no effect of juvenile growth on egg size when the effect of thermal embryonic conditions and adult size were controlled for.…”
Section: Discussionmentioning
confidence: 67%
“…Finstad & Jonsson (2012) showed that contrary to larval development, warm water during embryogenesis stimulated juvenile growth of salmon. To our knowledge, no study other than ours has demonstrated that thermal conditions experienced by embryos before hatching affect their adult body size.…”
Section: Discussionmentioning
confidence: 99%